Family nurse practitioner certification intensive review : fast facts and practice questions - Codina Leik, Maria T. (Springer Publishing Company, 2014)
Contains resources and application information for the certification exam, test-taking techniques for the ANCC and AANP, question and dissection analysis section, a review of primary care disorders and over 600 sample questions with answers and rationales.